Semi-hard cheeses - Eugster-Meier, Elisabeth; Fröhlich-Wyder, Marie‐Therese; Jakob, Ernst; Wechsler, Daniel; Morales, Maria Belén López; Licitra, Giuseppe; Berthier, Françoise; Papademas, Photis; Ardö, Ylva; Tavares, Tânia G.; Xavier, Malcata F.; Radulovic, Zorica; et al. (My University, 2017)
This chapter reviews various semi-hard cheeses, such as Appenzeller, Arzua-Ulloa Protected Designation of Origin (PDO), Castelmagno PDO, Comte PDO and Flaouna Cheeses, and explores its type, description and sensory characteristics, method of manufacture, and relevant research. Appenzeller is a semi-hard cheese which is very popular for its unmistakable spicy flavour produced through the application of a herbal brine during ripening. Arzua-Ulloa cheese is one of the most important Galician cheeses. Castelmagno PDO is a pressed semi-hard cheese. Flaouna is a Cyprus traditional cheese that is produced during Easter. The Fossa cheese from Sogliano received the PDO recognition in 2009. Herrgard cheese is the most popular cheese in Sweden. The Mahón-Menorca variety is a half-fat to full-fat pressed cheese which varied from semi-hard to hard cheese according to its ripening time. Full-fat pressed cheese made from Majorero goat's milk which varied from semi-hard to hard cheese, according to its ripening time.
Keywords: Appenzeller; Arzua-Ulloa PDO; Castelmagno PDO; Comte PDO; Flaouna cheese; Fossa cheese; Galician cheese; Mahón-Menorca